Correlation Between Quantitative Traits and Dry Land Sugarcane (Saccharum hybrid) Yield - Pranggono Mukti (Central Research Institute For Agriculture, 2021)
This study aims to determine the relationship (correlation) between quantitative traits and biomass of sugarcane Saccharum officinarum L.). The hypothesis that can be put forward in this study is that there is a positive and negative correlation between quantitative traits and biomass yield of sugarcane Saccharum officinarum L.). Sugarcane (Saccharum officinarum L.) is a plantation commodity that is widely developed in Indonesia because Indonesia's climate is suitable for the growth of sugar cane. In Indonesia, so far the cultivation of sugar cane is mostly done in paddy fields. However, because the need for rice continues to increase, more and more paddy fields are used for rice cultivation. This causes sugarcane land in paddy fields to shrink and shift to dry land or dry land. The average sugarcane yield on dry land in Java is only 67% of that of irrigated paddy fields. Meanwhile, the productivity of dry land outside Java is only 58% of that of irrigated paddy fields in Java. The decrease in sugarcane productivity is thought to be due to the shift in sugarcane planting from wet to dry land. Yield loss due to drought (water stress) can reach 40% of its production potential if it occurs during a critical plant phase. The success of efforts to obtain plants that have good quality and quantity of yield is greatly supported by the ability of plant breeders to obtain superior genotypes in the selection stage. In carrying out selection, plant breeders are often faced with the problem of making a choice of genotypic traits that are considered superior, therefore it is necessary to know the relationship (correlation) between quantitative traits and yields in these plants.